Crystal and molecular structure of series of triphilic ionic liquid-crystalline materials based on the 1, 2, 4-triazolium cation. Issue 44 (28th October 2022) - Riccobono, Alessio; Whitwood, Adrian C.; Parker, Rachel R.; Hart, Sam; Pace, Andrea; Slattery, John M.; Pibiri, Ivana; Bruce, Duncan W.
Abstract : The solid-state structure of sixteen triphilic triazolium salts with different anions is considered in terms of the potentially competing factors driving organisation. Abstract : Results from the determination of sixteen X-ray single crystal structures are reported for a series of 3-(4-alkoxyphenyl)-5-perfluoroalkyl-2, 4-dimethyl-1, 2, 4-triazolium salts with tetrafluoroborate, triflate or bistriflimide anions, in which the lengths of the alkoxy and perfluoroalkyl chains are varied systematically. On account of these cations having a hydrocarbon, fluorocarbon and ionic part, they are classified as triphilic. All of the tetrafluoroborate salts crystallised in the P 21 / c space group, most as acetone solvates, while for the bistriflimide salts, four different space groups were found although all contained a P 21 screw axis often with additional symmetry elements. Of the triflates, two crystallised in space groups with a P 21 screw axis and two in P 1̄. The organisation in the crystalline state tended to reflect the triphilic nature of the materials with cations and anions associating in repeating motifs, while the rest of the space was occupied by either hydrocarbon or fluorocarbon domains with only two exceptions.